An Evaluation of the Adoption of Cloud Accounting by SMEs in Zimbabwe - Dlamini, Banele; Schutte, Danie P. (International Journal of Economics and Financial Issues, 2024)
This paper investigated the use of cloud accounting by SMEs in Zimbabwe. The research used a quantitative approach and simple stratified random sampling techniques, stratifying according to firm size. A total of 132 questionnaires were used to collect data, and SPSS version 22.0 was used for the analysis. The study findings revealed a very low adoption of cloud accounting among SMEs in Zimbabwe. The foremost reasons for the low adoption rate of cloud accounting are a lack of awareness of the usage of cloud accounting, concerns about data security, and cost implications. The study further revealed that lack of training, data migration challenges, technical difficulties, integration issues, and concerns about data accuracy are the challenges faced by SMEs in implementing cloud accounting. The study recommends that SMEs prioritise training and skill development for their staff to build technical expertise in the utilisation of cloud accounting software. Furthermore, as the main stakeholder, the government should launch public awareness campaigns to educate small businesses about the benefits and opportunities of adopting cloud accounting technology.